2014
DOI: 10.1186/1471-2458-14-1238
|View full text |Cite
|
Sign up to set email alerts
|

Positive versus negative mental health in emerging adulthood: a national cross-sectional survey

Abstract: BackgroundThe dual continuum model suggests that positive mental health not only implies the absence of mental illness, but also constitutes an entity of its own. Measures that encompass both positive and negative mental health in young adults are rare. Thus, we assessed whether dimensions corresponding to positive and negative mental health could be identified in a sample of young individuals. Additionally, we explored how such dimensions were associated with potential health-related factors.MethodsWe obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 56 publications
(51 reference statements)
7
52
0
1
Order By: Relevance
“…Factor one was labeled as social dysfunction (items 1-6), factor two was labeled as anxiety (items 7-10) and factor 3 as loss of confidence (items 11-12); based on previous literature review and absolute value of 0.5 factor loading for each GHQ item represents the factor labeling. The findings from exploring the factor structure of GHQ-12 were similar to those of several other international versions [29,43]. These 3 factors explained 55% of the overall variance.…”
Section: Discussionsupporting
confidence: 65%
“…Factor one was labeled as social dysfunction (items 1-6), factor two was labeled as anxiety (items 7-10) and factor 3 as loss of confidence (items 11-12); based on previous literature review and absolute value of 0.5 factor loading for each GHQ item represents the factor labeling. The findings from exploring the factor structure of GHQ-12 were similar to those of several other international versions [29,43]. These 3 factors explained 55% of the overall variance.…”
Section: Discussionsupporting
confidence: 65%
“…However, it should be noted that while the current results indicate that a single dimension measure could fail to capture important aspects of an individual's mental health state, it is also crucial to consider the potential risk of 'creating' combined measures that do not possess strong psychometric properties by simply using data from separate illness and wellbeing focused single dimension measures. This notion is in line with findings from a previous study that similarly examined measures of positive and negative mental health in emerging adults, in a Swedish sample (Winzer et al, 2014).…”
Section: Comparison Of Single and Combined Approaches To Mental Healthsupporting
confidence: 92%
“…demographics, physical health) and across settings (Annells et al, 2010;Cappelli et al, 2012;Husky, Sheridan, McGuire, & Olfson, 2011), this limitation also draws attention to problems and concerns associated with this practice. While previous research on the GHQ has confirmed the measure as an appropriate tool for its original purpose, to detect "psychiatric morbidity", it is clear that as a popular and well-validated instrument, it may be employed for purposes beyond this (Winzer et al, 2014). Finally, it should also be acknowledged that the cross-sectional design of the current study represents a significant further limitation, as it eliminates the possibility of inferring causal relationships between factors and merely provides a snapshot of the sample characteristics at a specific point in time.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of psychiatry, it is pointed out that positive mental health, which is also known as (mental) well-being, should be distinguishable from negative mental health [11][12][13]. From results of previous studies, overgeneral autobiographic memory was reported as associated with mental health difficulties such as depression and PTSD.…”
Section: Introductionmentioning
confidence: 99%